Functionally graded AZ91/WC nanocomposite fabricated via friction stir processing using a novel way - Subhi A.D.; Abdulkareem M.H.; Hussein H.A. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In this work, functionally graded AZ91/WC nanocomposites were prepared by a novel multi-step chamber diameter reduction method. The WC nanoparticles were packed into chambers with graded diameters and processed by friction stirring using a tool with four-sided grooved probe. The functionally graded nanocomposites were fabricated at different tool rotational speeds (830, 960 and 1160 rpm) at a constant traverse speed and plunge depth of 40 mm/min and 0.1 mm, respectively. The properties of the functionally graded samples and AZ91 Mg alloy were evaluated by optical and scanning electron microscopy, energy dispersive spectroscopy, and other tests such as hardness, pin on disc wear and potentiodynamic polarization tests. The results showed that α-Mg and graded distribution of WC nanoparticles improved as the tool rotational speed increased. The hardness increased slightly with increasing the rotational speed of the tool. The results also revealed that the wear rate was decreased and corrosion resistance was improved by adding WC nanoparticles. Abrasive wear mode was the main mode of material removal during dry sliding, while cracks and pits were the main features of the corroded surface.